(untitled) (Research, Society and Development, 2022)
Several heavy metals and metalloids perform vital functions in living organisms. On the other hand, excessive exposure can cause possible negative morphological and physiological effects in reptiles. Anthropic action can directly interfere with the physiological imbalance of these animals, given that xenobiotics present in residues of human activities end up generating reactive oxygen species in the animal’s organisms, this condition is established when the production of free radicals overcomes antioxidant barriers. It is possible to carry out environmental monitoring for ecotoxicological studies using bioindicators and molecular biomarkers, using non-invasive sampling techniques, without harming the species. The objective of this literature review was to research information about the influence of heavy metals and their relationship with oxidative stress, anthropic actions, environmental bioindicators and their relationship with metabolic damage in reptiles. To carry out this review, articles in the scientific databases PubMed, CAPES journals portal, Google academic and SciELO were used. From this research, it was noted that human action has a harmful impact on both animals and man, since several metals and metalloids are disseminated through residues from industrial and domestic activities, and when discarded irresponsibly in marine or terrestrial biota can cause the bioaccumulation and the biomagnification phenomena. Thus exposed, this scenario leads to several metabolic damages, resulting in cell injury and organ dysfunction. The impact of the abusive use of heavy metals and contaminants in general can result in remodeling ecosystems, with direct effects on the conservation of reptiles.